The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/sji.12704
|View full text |Cite
|
Sign up to set email alerts
|

The D‐vitamin metabolite 1,25(OH)2D in serum is associated with disease activity and Anti‐Citrullinated Protein Antibodies in active and treatment naïve, early Rheumatoid Arthritis Patients

Abstract: The vitamin D metabolite 1,25(OH) D was inversely associated with disease activity and positively associated with ACPA in treatment naïve and inflammatory active early RA. The results indicate that in RA, both the degree of inflammatory activity, and the diagnostic sensitivity and specificity might affect-or might be affected by the level of vitamin 1,25(OH) D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…For instance, numerous studies revealed that single nucleotide polymorphisms (SNPs) of HLA-DRB1 (4046), STAT4 (47–52), and vitamin D receptor ( VDR ) (5358) were associated with RA and AITD. Scientists also observed that smoking and vitamin D deficiency had strong association with RA and AITD (5961). Furthermore, some researchers found that similar immune dysregulation appears in both RA and AITD.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, numerous studies revealed that single nucleotide polymorphisms (SNPs) of HLA-DRB1 (4046), STAT4 (47–52), and vitamin D receptor ( VDR ) (5358) were associated with RA and AITD. Scientists also observed that smoking and vitamin D deficiency had strong association with RA and AITD (5961). Furthermore, some researchers found that similar immune dysregulation appears in both RA and AITD.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Cooles et al reported no relationship between 25OHD and CRP, ESR, symptom duration, tender joint count (TJC), swollen joint count (SJC), or patients' global health visual analogue scale (GH-VAS) in a small cohort of 73 RA patients [13], and similarly Neilen et al found no evidence of low vitamin D in blood donor samples from patients in the pre-RA phase [14]. Conversely, other studies have reported an association of serum 25OHD or 1,25(OH) 2 D status with some markers of disease activity in early RA [15,16].…”
Section: Introductionmentioning
confidence: 96%
“…9 Organ-specific disorders typically aggregate within the same individual in autoimmune polyendocrine syndromes (APS), 10 which are yet distinct from systemic autoimmune conditions such as rheumatoid arthritis (RA) or systemic lupus erythematous (SLE). [11][12][13] Symptoms of AAD can be vague, and as a result, the disease is often diagnosed after the complete destruction of the adrenal cortex. 14 This, and restricted access to the affected organ in these patients, limits our knowledge of immunological processes occurring in the development of the disease.…”
Section: Introductionmentioning
confidence: 99%